Direct Aryloxylation/Alkyloxylation of Dialkyl Phosphonates for the Synthesis of Mixed Phosphonates. Issue 22 (7th May 2018) - Huang, Hai; Denne, Johanna; Yang, Chou‐Hsun; Wang, Haobin; Kang, Jun Yong
Abstract: A strategy for the direct functionalization strategy of inertial dialkyl phosphonates with hydroxy compounds to afford diverse mixed phosphonates with good yields and functional‐group tolerance has been developed. Mechanistic investigations involving both NMR studies and DFT studies suggest that an unprecedented highly reactive P V species (phosphoryl pyridin‐1‐ium salt), a key intermediate for this new synthetic transformation, is generated in situ from dialkyl phosphonate in the presence of Tf2 O/pyridine. Abstract : Mild thing, you make my heart sing : The application of Tf2 O to phosphorus chemistry was expanded to the generation of electrophilic P‐species. A metal‐free activation of stable dialkyl phosphonates was developed that enables the synthesis of diverse mixed phosphonates. The reaction proceeds under mild conditions and exhibits a broad substrate scope and excellent functional‐group tolerance. NMR studies and DFT calculations provide insight into the mechanism.